Targeting the Gut: A Systematic Review of Specific Drug Nanocarriers - Patrizia Garbati; Cristiana Picco; Raffaella Magrassi; Paolo Signorello; Ludovica Cacopardo; Mauro Dalla Serra; Maria Grazia Faticato; Maria De Luca; Francesco Balestra; Maria Principia Scavo; Federica Viti (MDPI AG, 2024)
The intestine is essential for the modulation of nutrient absorption and the removal of waste. Gut pathologies, such as cancer, inflammatory bowel diseases (IBD), irritable bowel syndrome (IBS), and celiac disease, which extensively impact gut functions, are thus critical for human health. Targeted drug delivery is essential to tackle these diseases, improve therapy efficacy, and minimize side effects. Recent strategies have taken advantage of both active and passive nanocarriers, which are designed to protect the drug until it reaches the correct delivery site and to modulate drug release via the use of different physical-chemical strategies. In this systematic review, we present a literature overview of the different nanocarriers used for drug delivery in a set of chronic intestinal pathologies, highlighting the rationale behind the controlled release of intestinal therapies. The overall aim is to provide the reader with useful information on the current approaches for gut targeting in novel therapeutic strategies.